A Comparison of Proteins among Various Influenza B Virus Strains by One-Dimensional Peptide Mapping - Nakamura, Kiyoto; Kitame, Fumio; Homma, Morio (Journal of General Virology, 1981)
SUMMARY The major virus-specific proteins (HA, NA, NP, NS1 and M) of five different isolates of influenza B virus (B/Lee/40, B/Osaka/2/70, B/Yamagata/1/73, B/Aomori/1/76 and B/Yamagata/26/77) were compared by limited proteolysis with Staphylococcus aureus V8 protease and subsequent polyacrylamide gel electrophoresis. The peptide patterns of matrix (M) proteins from all five strains were virtually identical. The nucleoproteins (NP) as well as the non-structural proteins (NS1) were also very similar among strains although the peptides of B/Lee/40 could be distinguished from those of the strains isolated from 1970 to 1977. In contrast, the peptides from haemagglutinin (HA) glycoproteins were largely different even among the strains isolated later than 1970. It therefore appears that the HA glycoproteins of influenza B virus are more changeable than any of the non-glycosylated proteins. Furthermore, it was found that the maps of HA1 were markedly different among strains while the maps of HA2 were very similar, which suggests that the structural changes in the HA polypeptide occur preferentially in the HA1 portion. The neuraminidase (NA) glycoproteins also showed strain-dependent differences in their mapping patterns.
Keywords: influenza B virus